Adolescents' time allocation and skill production. (December 2021) - Jürges, Hendrik; Khanam, Rasheda
Abstract: Using comprehensive time use data pertaining to Australian children (aged 10 to 15), we study the link between time inputs – educational activities, sports, and screen time – and cognitive as well as non-cognitive skills. Potential endogeneity of time inputs is addressed by adjusting for a comprehensive set of covariates, including initial skills and past inputs and outputs. We support our identifying assumption with a recently developed omitted variable test that exploits bunching of time use for certain activities at zero minutes. Results on relative effects of educational activities, sports, and screen time are summarized in specification curves. Our evidence suggests that educational activities at home improve cognitive skills. Compared to sports, screen time – including computer gaming and social networks – does not seem to harm cognitive skills, but increases internalizing problems among girls.